Pathological and Serum Biochemical Study of Liver Fluke Infection in Ruminants Slaughtered at ELFORA Export Abattoir, Bishoftu, Ethiopia (Global Journal of Medical Research, 2015)
A cross sectional study was conducted from September 2013 to July 2014 on a total of 284 ruminants (77 cattle, 99 sheep and 108 goats) to assess pathological and biochemical changes on liver infected with fluke at ELFORA export abattoir in Bishoftu, Ethiopia. Liver and blood samples of the same animals were collected using systematic random sampling. Gross and histopathological lesions and serum biochemical alterations were assessed. On the basis of gross pathological examination study animals were grouped into three: group-A (78.87%) showed no fasciola spp. and no visible gross lesion (taken as control groups), group-B (12.32%) confirmed with fasciola and fasciola indicative lesion and, group-C (8.80%) were co-infected (fasciola presence, fasciola indicative lesion and other lesions).
Keywords: ELFORA-abattoir; serum biochemicals; liver; liver fluke; pathological changes; ruminant; bishoftu; ethiopia